2019
DOI: 10.18502/kss.v3i17.4621
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Challenges of the Non-Directive Attitude in Person-Centred Counselling in Indonesian Culture

Abstract: Indonesian culture has influenced the way people perceive counselling, which shows the tendency towards avoidance attitudes. The situation presents a challenge towards the feasibility of person-centred counselling to be applied in Indonesia, as the counselling approach tends to come across with Indonesian culture. This paper aims to critically discuss the potential challenges of working with the Indonesian client from a cultural point of view and the readiness of a counsellor in terms of knowledge about non-dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…Understanding the reasons for school bullying could not be separated from recognising the cultural background and social hierarchy of the victims and perpetrators [29]. Similar to other Asian countries, Indonesian culture tends to uphold the value of collectivism within diverse ethnic groups [54]- [56]. On the one hand, living in a diverse society benefits people to establish their sense of respect and tolerance towards others.…”
Section: "I Felt Anxious and Was Terrified To Meet The Bullies In The...mentioning
confidence: 99%
“…Understanding the reasons for school bullying could not be separated from recognising the cultural background and social hierarchy of the victims and perpetrators [29]. Similar to other Asian countries, Indonesian culture tends to uphold the value of collectivism within diverse ethnic groups [54]- [56]. On the one hand, living in a diverse society benefits people to establish their sense of respect and tolerance towards others.…”
Section: "I Felt Anxious and Was Terrified To Meet The Bullies In The...mentioning
confidence: 99%
“…This study found that trainee counsellor's cultural background is one of challenges in experiencing congruence in therapeutic relationship. Every culture has different perspectives in responding to the client's situation that can be a barrier to experience congruence in practice (Sutanti, 2019). Counsellor's condition of worth is caused by different value, belief and language that can be a barrier for the counsellor to understand the client (Jayne, 2013;Tudor, 2013).…”
Section: Experiencing Congruence In Practicementioning
confidence: 99%
“…Karena itu, disamping nasihat keuangan, mahasiswa pasti membutuhkan bantuan dalam bentuk materi (Scott-Clayton, 2012). Pertimbangan lain adalah karena konseling merupakan hal yang tidak umum dilakukan di Indonesia, termasuk di kalangan mahasiswa (Sutanti, 2019). Hal ini terbukti dari hasil statistik deskriptif responden di tabel 1 yang menunjukkan bahwa jumlah mahasiswa yang mencari bantuan materi lebih besar dibanding mahasiswa yang mencari bantuan dalam bentuk nasihat.…”
Section: Hasil Dan Pembahasanunclassified
“…Sejalan dengan hasil penelitian terdahulu yang dilakukan oleh (Sutanti, 2019), dari hasil penelitian ini dapat terlihat bahwa jasa profesional di bidang keuangan belum terlalu dikenali oleh masyarakat Indonesia, dalam hal ini mahasiswa,. Hasil penelitian ini membuktikan bahwa banyak mahasiswa yang mengalami kesulitan keuangan dan membutuhkan bantuan keuangan, namun belum pernah datang ke pihak profesional.…”
Section: Penutupunclassified